Analisa Kerusakan Perkerasan Jalan Menggunakan Metode Pavement Condition Index (PCI) Studi Kasus: Kel. Lasada Kec. Unaaha Kab. Konawe - Sakti, Putra; Alkadri, Alkadri; Islamiyati, Puji Azizah Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Road damage is a problem caused by various factors, including excessive repetitive traffic loads, temperature and rainfall effects, and poor initial construction quality. Roads that are not properly designed and maintained will experience a decline in both structural and functional quality, resulting in reduced service performance for users. The impacts of road damage include traffic flow disruption, decreased comfort, and increased safety risks. The condition and type of vehicles passing over the road also significantly affect the pavement design and structural durability. A study on the road section in Lasada Village, Unaaha District, shows that the increased traffic volume on the regency road connecting Tuoy Village and Ambekaeri Village has led to various types of damage, such as cracking and potholes. With an approximate length of 1 km, width of 7.2 m, and pavement thickness of 15 cm, this road has experienced a reduction in load-bearing capacity due to unmet construction standards. Consequently, the level of service and comfort for road users has decreased significantly.